Speech Acts of Advising in Selected News Texts about Coronavirus (Journal of the College of Basic Education, 2024)
After the invading of Coronavirus in 2019 in China, The world Health Organization has declared this virus as a pandemic. The virus outbreaks among countries terrifying manner which makes governments take some quick decisions to stop it. Government all over the world employes TV channels and media to deliver instructions and advices to their peoples. But, this time the advice and instructions are different in style and language, since there is a crisis which may destroy the whole country, as what has happened in Ital pandemicly. Therefore, the speech act of advising which is used under this circumstances is a bit different for imposing more emphasis to face that danger. Advising people needs to be more directive and imperative. This study hypothesizes that under serious crisis, speech act of advice tends to be more directive and imperative to make the language receiver takes the advice in his/her consideration. This study tries to answer the following question: Do strategies in performing speech act of advice under a common crisis differ between government and Tv Channels? The study analyses ten texts from two different news channels. The first five texts are taken from Kurdistan 24 Channel and the other five are taken from BBC NEWS Channel.The study reaches to the findings that under serious crisis, there is no difference between western and esteran government in the strategies used to direct their people. In both channels, the speech act of advice tends to be direct and imperative more than other strategies to express it.